2023
DOI: 10.1186/s12909-023-04535-3
|View full text |Cite
|
Sign up to set email alerts
|

Full-sized realistic 3D printed models of liver and tumour anatomy: a useful tool for the clinical medicine education of beginning trainees

Abstract: Background Simulation-based medical education (SBME) and three-dimensional printed (3DP) models are increasingly used in continuing medical education and clinical training. However, our understanding of their role and value in improving trainees’ understanding of the anatomical and surgical procedures associated with liver surgery remains limited. Furthermore, gender bias is also a potential factor in the evaluation of medical education. Therefore, the aim of this study was to evaluate the educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…For the moment, 3D printing can realistically replicate the geometric structures of anatomical models and can replicate multiple colors and textures, but without precision in mimicking the mechanical properties of soft tissues. This makes it a useful tool, depending on the level of realism required, for several educational and surgical planning purposes [86][87][88][89][90].…”
Section: Mechanical Properties: Seeking To Mimic Real Tissuementioning
confidence: 99%
“…For the moment, 3D printing can realistically replicate the geometric structures of anatomical models and can replicate multiple colors and textures, but without precision in mimicking the mechanical properties of soft tissues. This makes it a useful tool, depending on the level of realism required, for several educational and surgical planning purposes [86][87][88][89][90].…”
Section: Mechanical Properties: Seeking To Mimic Real Tissuementioning
confidence: 99%
“…A growing body of evidence suggested that SBME was effective for teaching clinical knowledge, skills, and behaviors compared with traditional methods. Studies have found the effect of SBME in cardiology [ 11 ], anesthesiology [ 12 ], and anatomy [ 13 ]. It might be beneficial to use SBME in clinical research curriculum.…”
Section: Introductionmentioning
confidence: 99%